Topographie, urbanisme et gestion des réseaux d’eau à Autun/Augustodunum (Saône-et-Loire) : une nouvelle image de la capitale de cité - Laetitia Borau (Gallia)
The recent researches shed a new light on Augustodunum, Ædui’s chief-town, thanks to a comparison between topographic, urbanistic and hydraulic data. We could identify more than 234 structures linked to water management. Although two aqueducts (Montjeu and Montdru) had already been studied in detail thanks to on-site operations, the novelty of this research lies in the exhaustive analysis of the inner town. This work highlights, for the first time in its context, the town’s water supply system, unknown until now, which consists in wood or lead pipes, the importance of urban amenities, especially private fountains, and the density of the sewer system which takes nearly half of the corpus. This thorough study of Augustodunum, where natural water resources were plentiful, proves the importance of urban equipment devices linked to water in a Roman town of northern Gaul.